The impact of mediterranean diet in psoriasis - Franklind matthew; Marsha Kurniawan (Indonesian Nutrition Association, 2022)
Introduction: Psoriasis is a chronic, immune-mediated inflammatory skin disease characterized by systemic inflammation with skin, joint and metabolic involvement. Several risk factors have been recognized in the etiology and pathogenesis of psoriasis, including family history and environmental risk factors, such as diet, obesity, smoking, stress, and alcohol. Dietary patterns, such as the Mediterranean diet have been proposed to alleviate chronic inflammation. In this literature review, we aimed to thoroughly review the impact of MD in psoriasis.